Correction: Attitudes, practices, and zoonoses awareness of community members involved in the bushmeat trade near Murchison Falls National Park, northern Uganda. - BreeAnna M Dell; Marcy J Souza; Adam S Willcox (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0239599.].